Pengembangan Modul Ajar Berbasis Model Pembelajaran Inquiry untuk Meningkatkan Kemampuan Komunikasi Matematis Siswa SMA - Sudane, I Wayan; Fitrianti, Fitrianti; Adriansyah, Adriansyah (Program Studi Pendidikan Matematika, 2024)
This Mathematical communication skills are very important for students in solving mathematical problems. Less than optimaluse of teaching modules at school can have an impact on students’ low mathematical communication skills. This research aims to describe the stages of developing a teaching module based on the inquiry learning model that is valid, effective and practical and can improve students’ mathematical communication abilities. The method in this research uses the ADDIE development model which consists of the first stage of analysis, the second stage is design, namely preparing the conceptual framework of the learning model and tools, then the third stage of development is the stage that involves validation testing or assessing the suitability of the media, then the implementation stage, namely the trial stage. Product and finally the eval____uation stage, namely the stage ofreviewing the stage that the researcher has gone through or carried out. Data collection techniques consist of tests and non-tests. The results of the research at the definition and design stages gave rise to the elements of the teaching module in the form of the front of the teaching module, the content components of the teaching module, and the closing part of the teaching module. The development stage resulted in an average material expert validation assesment of 96.87%, an average media expert validation assesment of 62.5%, a standart gain value for mathematical communication skills of 0.3 and an average response questionnaire for students and teacher of 100%. Based on this, the teaching module based on the inquiry learning model is declared valid, effective and practical and can improve the mathematical communication abilities of class XI IPA F3 students at SMA Negeri 2 Luwuk.